Rootstocks for ‘Valência’ sweet-orange in Santa Catarina in the context of plant size and spacing reduction - Brugnara, Eduardo Cesar; Roveri Sabião, Rafael; Aparecida Castilho Maro, Luana (Revista Ceres, 2025)
Citrus orchards have been planted in higher tree densities, which encourage the use of rootstocks that reduce scion tree size. The performance of low-vigor rootstocks with ‘Valência’ orange is not well known, especially in southern Brazil. The objective of this work is to compare the agronomic performance of ‘Valência’ sweet orange grafted on seventeen rootstocks in western Santa Catarina, Brazil, and analyze the results in light of the search for small trees for orchards with narrower spacing. An experiment was conducted over 10 years for evaluation of seventeen rootstocks, concerning tree size, yield and fruit quality. The rootstocks were classified in Standard (six genotypes, including ‘Swingle’, main rootstock in Santa Catarina), Super-standard (two genotypes), Semi-standard (seven genotypes) and Dwarf (two genotypes). An estimated hectare yield was calculated after a tree spacing adjustment based on tree diameter. In conclusion, the citrandarin ‘San Diego’ forms trees similar in size to the widespread citrumelo ‘Swingle’, but is more productive, and maintains the quality of the fruit. ‘Fepagro C37 Dornelles’ reduces ‘Valência’ tree size, facilitates fruit harvest and induces it to produce big, good quality fruits. Dwarf rootstocks lead to a low hectare yield even in reduced space orchards.